A safety evaluation of sucroferric oxyhydroxide for the treatment of hyperphosphatemia. Issue 12 (2nd December 2021) - Sprague, Stuart M.; Ketteler, Markus
ABSTRACT: Introduction: Hyperphosphatemia is a common complication as chronic kidney disease (CKD) progresses and most patients undergoing dialysis are prescribed oral phosphate binder therapy to control serum phosphate concentrations. Sucroferric oxyhydroxide is an iron-based phosphate binder approved for the treatment of hyperphosphatemia in CKD patients on dialysis. Areas covered: This article reviews key safety and effectiveness data for sucroferric oxyhydroxide from both prospective clinical trials and real-world observational studies. Expert opinion: Sucroferric oxyhydroxide potently binds dietary phosphate in the gastrointestinal (GI) tract, resulting in effective reduction of serum phosphate concentrations with a relatively low daily pill burden. Data from clinical trials and real-world observational studies show sucroferric oxyhydroxide has a favorable safety and tolerability profile. The most frequent side effects observed with sucroferric oxyhydroxide are GI-related, mainly discolored (black) stools and mild or moderate transient diarrhea, both of which are manageable. There is minimal systemic iron absorption from sucroferric oxyhydroxide, and therefore the drug is associated with a low risk of iron accumulation. Sucroferric oxyhydroxide also displays low potential for drug–drug interactions with other commonly prescribed oral medications. Overall, sucroferric oxyhydroxide offers an effective and well-tolerated treatment option for the management of hyperphosphatemia.